2018
DOI: 10.3390/children5040049
|View full text |Cite
|
Sign up to set email alerts
|

Ponseti Technique for the Management of Congenital Talipes Equinovarus in a Rural Set-Up in India: Experience of 356 Patients

Abstract: Congenital talipes equinovarus (CTEV), also known as clubfoot, is a complex congenital deformity of the foot that, left untreated, can limit a person’s mobility by making it difficult and painful to walk. Worldwide, 80% of children born with clubfoot are in low- and middle-income countries. The management of clubfoot has a long history. Non-operative management did not become popular, as an increasing number of orthopaedists started leaning towards surgical treatment. The late Dr. Ignacio Ponseti developed a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Rohit malhotra et al ( 2018)) done a study in rural setup of India in 356 patients reported 94.5% good results [31]. Similar pa ern of results were also observed in many studies [24,32,33].…”
Section: Resultssupporting
confidence: 63%
“…Rohit malhotra et al ( 2018)) done a study in rural setup of India in 356 patients reported 94.5% good results [31]. Similar pa ern of results were also observed in many studies [24,32,33].…”
Section: Resultssupporting
confidence: 63%
“…[4][5][6] Also, the results of our study are comparable to other studies done about this technique. 7,8 The mean age of children at diagnosis was 7.8 months with a range from 3 days to 36 months. 72.6% (n=61) children were below six months of age, and 52.5% (n=32) of these had bilateral clubfoot.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, use gentle manipulation to correct the deformity. The costs incurred are also more affordable than surgical treatment (Malhotra et al, 2018;Mustari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%